Development of a supervisory system for maintaining the performance of remote energy management systems / Johan Nicolaas du Plessis - Du Plessis, Johan Nicolaas (2015)
Energy services companies (ESCOs) typically implement energy management systems (EMSs) as part of Demand-Side Management (DSM) projects on South African mines. After DSM project completion, the mine becomes responsible for maintaining the performance of the EMS. Due to a lack of experience in using specialised EMSs, mines typically contract ESCOs for EMS maintenance. However, maintaining a large number of EMSs remotely is a resource-intensive task because of time wasted on daily monitoring and travelling to perform on-site maintenance. For the same reason, remote maintenance technologies have become widely used to maintain cellular devices, vehicles and industrial equipment. Mine EMSs typically control production-critical systems that in turn ensure safe working conditions underground. EMSs execute highly specialised control philosophies to achieve electrical energy management, while ensuring safe and productive system operation. None of the work done on remote maintenance, however, provides an integrated solution to maintain the performance of a growing number of these specialised EMSs. As part of this study, a supervisory system was developed to optimise remote maintenance of different EMS technologies. The supervisory system builds on the fundamentals of existing remote maintenance technologies, complemented by comprehensive diagnostics of specialised EMS technologies. This is possible through automated diagnostics of EMS components, the control philosophy and overall EMS performance. Maintenance management forms part of the supervisory system to ensure that maintenance is performed with optimal efficiency. A system implementation was executed to prove the feasibility of the supervisory system. The functional operation of the system was verified with pre-set scenarios that simulated day-to-day operation and common fault diagnostic events. As part of the case studies conducted for this thesis, the supervisory system was integrated with three distinct EMS technologies implemented on South African mines. To support the results of these case studies, the system validation was extended through integrations with seven additional EMSs. For the first time, a supervisory assessed the condition of the EMS components, the control philosophy and DSM performance comprehensively. The results (obtained over a period of more than six months) indicated that the average operational availability of EMS components improved from 90% to 97%. The average EMS performance improved from 1.8 MW to 2.5 MW, an improvement of 39%. The resulting electricity cost reduction achieved on the case studies accumulated to approximately R6 million during the respective assessment periods. The supervisory system facilitated efficient EMS maintenance, thus reducing the risk of unsafe working conditions and production interruptions. The system also allowed maintenance personnel to improve the diagnostic process continually, thus aligning with the standards documented in ISO 50001:2011 (ISO, 2011) regarding continual improvement of electrical energy management initiatives. The new supervisory system is scalable, thus an ESCO can maintain the performance of a growing number of EMSs remotely. Results of this study support further supervisory system integration with compatible EMS technologies, and expansion to new EMS technologies. The modular design of the supervisory system provides a basis for the development of a cross-industry platform for maintaining EMS performance. === PhD (Computer and Electronic Engineering), North-West University, Potchefstroom Campus, 2014